Pengaruh Pemahaman Agama Islam terhadap Perilaku Sosial Siswa di SMP Negeri 1 Ciomas - Fida Khotimah; M. Kholil Nawawi; Abrista Devi (Fakultas Syariah IAIN Laa Roiba Bogor, 2023)
The way students behave today needs serious attention. Because many things are not in accordance with the understanding of Islam that is shown in the family and at school, it is due to a lack of understanding of Islam by students. This study aims to determine 1). Understanding of Islam in class VIII at SMP Negeri 1 Ciomas, 2). Social Behavior of Class VIII students at SMP Negeri 1 Ciomas, and 3). The influence of Islamic religious understanding on the social behavior of eighth grade students at SMP Negeri 1 Ciomas. The approach used is quantitative with a survey method, namely a data collection carried out in the form of a questionnaire/questionnaire, which is then disseminated to respondents. The selected respondents are the return of 59 students of class VIII. The results of this study indicate that the understanding of Islam in class VIII is in the good category. This is based on the number of respondents' answers with the answer